Apoptotic cell clearance by bronchial epithelial cells critically influences airway inflammation - Juncadella, Ignacio J. (2012)
Lung epithelial cells can influence immune responses to airway allergens(1,2). Airway epithelial cells also undergo apoptosis after encountering environmental allergens(3); yet, relatively little is known about how these are cleared, and their effect on airway inflammation. Here we show that airway epithelial cells efficiently engulf apoptotic epithelial cells and secrete anti-inflammatory cytokines, dependent upon intracellular signalling by the small GTPase Rac1. Inducible deletion of Rac1 expression specifically in airway epithelial cells in a mouse model resulted in defective engulfment by epithelial cells and aberrant anti-inflammatory cytokine production. Intranasal priming and challenge of these mice with house dust mite extract or ovalbumin as allergens led to exacerbated inflammation, augmented Th2 cytokines and airway hyper-responsiveness, with decreased interleukin (IL)-10 in bronchial lavages. Rac1-deficient epithelial cells produced much higher IL-33 upon allergen or apoptotic cell encounter, with increased numbers of nuocyte-like cells(1,4,5). Administration of exogenous IL-10 ‘rescued’ the airway inflammation phenotype in Rac1-deficient mice, with decreased IL-33. Collectively, these genetic and functional studies suggest a new role for Rac1-dependent engulfment by airway epithelial cells and in establishing the anti-inflammatory environment, and that defects in cell clearance in the airways could contribute to inflammatory responses towards common allergens.